Saudi Oncology Society and Saudi Urology Association combined clinical management guidelines for prostate cancer 2017 - Aljubran, Ali (Urol Ann, 2018)
This is an update to the previously published Saudi guidelines for the evaluation and medical and surgical management of patients diagnosed with prostate cancer. Prostate cancer is categorized according to the stage of the disease using the tumor node metastasis staging system 7(th) edition. The guidelines are presented with supporting evidence levels based on a comprehensive literature review, several internationally recognized guidelines, and the collective expertise of the guidelines committee members (authors) who were selected by the Saudi Oncology Society and Saudi Urological Association. Local factors, such as availability, logistic feasibility, and familiarity of various treatment modalities, have been taken into consideration. These guidelines should serve as a roadmap for the urologists, oncologists, general physicians, support groups, and health-care policymakers in the management of patients diagnosed with adenocarcinoma of the prostate.